On Geortonyms Representing Flower Flowers in Uzbek Language (Texas Journal of Philology, Culture and History, 2024)
The article describes the linguistic features of geo-tonyms, special famous names representing flowers: their occurrence, naming, lexical basis, structural models, and linguistic and cultural aspects.